The normative method of positive economic theory (1997)
Economists tend to designate as normative economics that part of the theory which, according to the theorems of welfare or efficiency, create the foundation of political economy. This article defends two theses: first, that the normative is not only a part of economic theory, but also the method of building the positive economic ideas in the currently dominant neoclassical theory. This method allows that theory to claim to unify economic thought, eliminating the possibility and the necessity for alternative approaches. Nevertheless, and this is the second thesis, there are no legitimate theoretical reasons to accept this methnodology; thus it is impera tive to build a new basic theory.